Análise da influência da ação do vento em galpões industriais no município de Itaituba-PA: um estudo de caso - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This paper constitutes a case study conducted in the Itaituba region, focusing on analyzing the influence of wind on industrial warehouses. The main objective is to examine the structure of these warehouses according to the standards established by NBR, as well as to investigate how the wind behaves within in these structures. The methodology adopted was based on NBR guidelines, combined with a meteorological analysis of the municipality to understand how the structure would react to the predicted wind gusts in the region. The results indicated that the data obtained fell short of the standard set by the codes, suggesting that wind played a fundamental role in this scenario. Therefore, it is crucial to analyze building structures according to the standards and consider the action of wind to ensure their safety and effectiveness.
Keywords: Influência do vento; Galpões industriais; Rajadas de vento; Estrutural.; CNPQ:: CIÊNCIAS EXATAS E DA TERRA